INCOME-HEALTH NEXUS IN SUB-SAHARAN AFRICA: EVIDENCE FROM HETEROGENEOUS PANEL MODELS - Odusanya, Ibrahim; Atanda, Akinwande (The European Journal of Applied Economics, 2018)
An attempt is made in this research to examine the relationship betweenincome and health by testing the Absolute Income-Health Hypothesis(AIH). The study primarily focuses on 34 Sub-Saharan Africa (SSA)countries for the period of 2001-2016. The data for the study were mainlysourced from World Development Indicators (WDI) and the WorldHealth Organization (WHO) Global Health Observatory Data Repository.Using heterogeneous slopes modelling set-up that incorporates seriesof non-stationarity, cross-section dependence, and group-specifictrends, we failed to find evidence in support of the AIH. Our empiricaloutcome cast doubts on the robustness of previous studies that ignoredsuch modelling attributes, while we deduced that methodology mattersin analysing income-health nexus and testing the validity of the AIHfor cross-section of countries. By contrast, we find income to be an insignificantdeterminant of health in SSA compared to health spendingand improved sanitation.
Keywords: Health; Income; Sub-Saharan Africa; Heterogeneous slope; Cross-section Dependence